Molecular characterization and methylation status of torque teno virus isolation among hepatitis patients in a public hospital in Pahang, Malaysia - Hazanuddin, Siti Nurzulaikha (2020)
Hepatitis diseases also known as asymptomatic at the early stage of infection. There are viruses classified as commensal yet opportunistic pathogens with a high infection rate, including anellovirus. Torque teno virus (TTV) is a small, nonenveloped and circular single-stranded DNA anellovirus that infects the human population worldwide, especially hepatitis patients. A high prevalence of TTV was reported from various countries to include within the Asian continent. However, there is no information regarding the TTV prevalence among hepatitis patients in Malaysia. Hence, this study decided to determine the genotype of TTV as well as to construct the phylogeny tree of TTV isolated among the hepatitis community in Hospital Tengku Ampuan Afzan (HTAA) Kuantan. Other than that, this study aims to determine the mutation by DNA methylation in the CpG distribution of TTV isolates. The sample subject selected is hepatitis patients who attended HTAA for a medical appointment. A total of 137 hepatitis patients have been recruited and the plasma DNA was tested with three sets of primers by using the standard PCR method to amplify the coding and noncoding region of TTV. It was discovered that 87.5% and 73.7% of the subjects showed the presence of the noncoding region of TTV when two different sets of primers were used (UTR(a) and UTR(b)). Meanwhile, for the presence of the N22 region which is the selected coding region located in ORF1 specifically among Group 1 TTV, 20% of positivity were shown. The other 80% of positively detected TTV isolates without N22 region could not be classified into any groups as it is require further sequence analysis. Out of 101 positive UTR(b) samples which have been subjected for sequencing, only 41 samples produce complete readable sequences which belong to TTV genome. Low concentration amplicon and samples presented with multiple bands which have the possibility of co-infection were excluded from the analysis. By the construction of the phylogeny tree, conserved TTV isolates in hepatitis patients were identified in Clade A with the majority of numbers. Despite that, TTVMY02 is the first TTV Malaysian isolate from hepatitis patients with partial whole genome sequence of 3,265 kb and was determined by phylogeny relation to have a high identity percentage with KAV isolate, which grouped in Group 2. The protein translated region for all ORFs in TTVMY02 isolates were well described on its physiochemical properties; and ORF1 and ORF2 appeared to be more hydrophobic while ORF3 more hydrophilic. Lastly, the selected TTV Malaysian isolate was further investigated for the methylation properties in the region consist of the highest CG percentage among a few CpG island by bisulfite sequencing and methylation-specific PCR. The result showed the CpG methylation in the TTV genome with 80% proved to be methylated in the selected island. Although the methylation of CpGs which is an addition of methyl group at cytosine base is considered as mutation, the alteration could be the way for the TTV virus to escape from the immune cells. Besides, there is no further investigation on the effect of TTV DNA methylation towards a cell line, but the postulation could be made based on PPV genome structure due to the similarity shared between both viruses. In conclusion, the characteristics of the TTV genome described in the study could be suggested that the virus is a non-pathogenic virus yet potentially leading to latent infection without any outbreak or disease outcome.